Comprehensive review of SGLT2 inhibitors’ efficacy through their diuretic mode of action in diabetic patients - Lam-Chung, Cesar Ernesto (Frontiers in Endocrinology, 2023)
SGLT2 inhibitors (SGLT2i) are now of the mainstay therapy for both diabetes and heart failure. Post-hoc publications, meta analysis and congresses presentations of the eight SGLT2i Cardiovascular Outcomes trials (CVOTS) done in diabetic patients, constantly echo that this class of drug decrease mortality, reduce cardiovascular events, prevent heart failure and kidney disease. This review of Medical agencies SGLT2i analysis (FDA, EMA) help to understand the reality of SGLT2i results in those trials, avoiding to consider observational and statistically undemonstrated endpoints as validated. They also confirmed the unique diuretic mode of action of SGLT2i, promoting osmotic diuresis, and its potential adverse events secondary to hypovolemia and hematocrit increase. They also support the understanding that the beliefs in SGLT2i morbi-mortality benefits are largely overstated mostly based on undemonstrated endpoints. Finally, it makes clear that SGLT2i antidiabetic action, secondary to its renal mode of action, plataued after few months and decrease strongly overtime, questioning its long term interest to maintain diabetic patients’ HbA1c below 7%. Also this effect in patients with renal impairment is quasi nul. We think that this review would be highly helpful to every physician treating diabetic patients to better balance belief and reality of SGLT2i prescription effects.